The decision delivery interval in emergency caesarean section and its associated maternal and fetal outcomes at a referral hospital in northern Tanzania: a cross-sectional study - Birjna A. Hirani; Bariki L. Mchome; Nicholaus S. Mazuguni; Michael J. Mahande (BMC, 2017)
Abstract Background Decision delivery interval (DDI) is the time line between a decision to conduct an emergency caesarean section and actual delivery of the baby. Prolong DDI constitute a third phase delay in provision of emergency obstetric care. Intervention designed to minimize DDI are vital, in attempt to prevent maternal morbidity and neonatal morbidity and mortality. The feasibility and practicability of the recommended DDI in recent studies have been questioned especially in limited resource setting and therefore the objective of our study was to determine the DDI and its associated fetalmaternal outcomes at a tertiary referral hospital in Tanzania. Methods This was a retrospectivecross-sectional study of inpatient cases who underwent emergency caesarean section from January to September 2014. Data were collected from birth registry and case files of patients. Data analysis was performed using statistical package for social science (SPSS) version 22.0. Odds ratio (ORs) and 95% confidence interval for maternal and fetal outcomes associated with DDI were estimated using Logistic regression models. A p-value of less than 5% was considered statistically significant. Results A total of 598 women who underwent emergency caesarean section were recruited. The median Decision Delivery Interval was 60 min [IQR 40-120]. Only 12% were operated within 30 min from decision time. Shortest DDI was seen in patients with Cephalopelvic Disproportion (CPD) and uterine rupture (40 min and 45.5 min) as compared to other conditions. Cases with impending uterine rupture, cord prolapse, APH and fetal distress showed to have shorter DDI. There was no significant association between DDI and neonatal transfer,1st and 5thminute Apgar score, maternal blood loss (OR: 5.79; 95% CI 0.63-1.64) and hospital stay (OR: 1.02; 95% 0.63-1.64). Conclusions Contrary to the recommended DDI by ACOG & AAP of 30 min is not feasible in our setting, time frame of 75 min could be acceptable but clinical judgment is required to assess on the urgency of caesarean section in order to prevent maternal and neonatal morbidity and mortality.